The Choice Between External and Domestic Debt in Financing Budget Deficits : The Case of Central and West African Countries - Beaugrand, Philippe (IMF Working Papers; Working Paper, 2002)
The paper reviews the principles and practical considerations involved in the choice between foreign and domestic financing of fiscal deficits, and derives a series of recommendations broadly applicable to Central and West African countries. The paper develops a simple analytical framework and shows that highly concessional external debt is usually a superior choice to domestic debt in terms of financial costs and risks, even in the face of a probable devaluation. The paper stresses the importance of the availability and terms of financing, and of overall long-term debt sustainability. It concludes that these countries need to take a gradual approach to domestic debt financing, beginning with the issuance of short-term bills, and ensure a solid track record of meeting their debt-service obligations.